Synthesis and Spectroscopic Characterization of Some New Axially Ligated Indium(III) Macrocyclic Complexes and Their Biological Activities - Gauri D. Bajju; Altaf Ahmed; Deepmala Gupta; Ashu Kapahi; Gita Devi (Bioinorganic Chemistry and Applications)
The synthesis and spectroscopic characterization of new axially ligated indium(III) porphyrin complexes were reported. Chloroindium(III) porphyrin (TPPIn-Cl) was obtained in good yield by treating the corresponding free base with indium trichloride. The action of the different phenols on chloroderivatives (TPPIn-Cl) led to the corresponding phenolato complexes (TPPIn-X). These derivatives were characterized on the basis of mass spectrometry, 1H-NMR, IR, and UV-visible data. The separation and isolation of these derivatives have been achieved through chromatography. The spectral properties of free base porphyrin and its corresponding metallated and axially ligated indium(III) porphyrin compounds were compared with each other. A detailed analysis of UV-Vis, 1H-NMR, and IR suggested the transformation from free base porphyrin to indium(III) porphyrin. Besides, 13C-NMR and fluorescence spectra were also reported and interpreted. The stability of these derivatives has also been studied through thermogravimetry. The complexes were also screened for anticancerous activities. Among all the complexes, 4-MePhO-InTPP shows highest anticancerous activity. The title complexe, TPPIn-X (where X = different phenolates), represents a five-coordinate indium(III) porphyrin complex in a square-pyramidal geometry with the phenolate anion as the axial ligand.